Epigenetics in agriculture - King, Graham (Henry Stewart Talks, 2013)
Climate change: a global challenge for agriculture, Crop plasticity and genotype x environment interactions, Molecular basis of epigenetics, Mapping epigenetic marks and epi-alleles, Modulation of crop development and plasticity